PENERAPAN MODEL GROUP INVESTIGATION BERBASIS MEDIA HERBARIUM MENGGUNAKAN APLIKASI PICTURETHIS-PLANT IDENTIFIER UNTUK MENINGKATKAN KREATIVITAS DAN HASIL BELAJAR SISWA - Perayanti Sinaga, Dian; Rajagukguk, Salome; Rolita, Ria (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2024)
This study aims to determine the effect of implementing the group investigation model based on herbarium media using the PictureThis-Plant Identifier application on students' creativity and learning outcomes. This research is a field research with a quantitative approach using the Pretest-Posttest Control Group Design research design. The results showed that the implementation of the group investigation model based on herbarium media using the PictureThis-Plant Identifier application had a significant effect on increasing students' learning creativity. This is indicated by the value of tcount > ttable (45.443 > 1.681) at a significance level of 0.05. The experimental class using this learning model had a higher average score of learning creativity compared to the control class. The implementation of the group investigation model based on herbarium media using the PictureThisPlant Identifier application also had a significant effect on improving student learning outcomes. The data analysis showed that the value of tcount > ttable (92.217 > 1.681) at a significance level of 0.05. The average posttest score of the experimental class (82.50) was higher than the control class (77.50).